Monster house - Buscemi, Steve, 1958-; Gyllenhaal, Maggie, 1977-; Kenan, Gil; Lee, Jason, 1970-; Schrab, Rob; Starkey, Steve (United States : Sony Pictures Entertainment, 2006)
Tres adolescentes descubren que la casa vecina esta realmente viva, respira, y es un temible monstruo.
Copyright: Columbia Pictures Industries, Inc. DCR 2006; PUB 21Jul06; REG 21Jul06; PA1-322-810.
DISPONIBLE
Not viewed.
Sources used: copyright data base; copyright data sheet; Internet movie database, viewed on Feb. 1, 2007; Variety, July 10, 2006.
Summary taken from Internet movie database.
Executive producers, Robert Zemeckis, Steven Spielberg, Jason Clark ; camera, Xavier Perez Grobet ; editors, Adam P. Scott, Fabienne Rawley ; music, Douglas Pipes ; production designer, Ed Verreaux ; visual effects art directors, Michael Scheffe, George Suhayda ; visual effects supervisor, Jay Redd ; animation supervisor, Troy Saliba.
Keywords: Comedia -- Animación -- Largometra para televisión; Fantasía -- Animación -- Largometra para televisión; Misterio -- Animación -- Largometra para televisión